Exploring the HPLC Profiling and Antioxidant Potency in Methanolic Extracts of Curcuma longa L. Rhizomes - Shukla, Babita; Kushwaha, Poonam (Drug Research, 2024)
In this exploration of Curcuma longa Linn., commonly known as turmeric, renowned for its therapeutic history, our study focuses on the bioactive compound curcumin. We established and validated an HPLC method for precise curcumin quantification, complemented by an examination of total phenolic and flavonoid content, as well as antioxidant capabilities in a methanolic extract from C. longa rhizomes obtained through a methanol-based Soxhlet extraction. The HPLC analysis utilized a C18 column with a mobile phase of 70:30 V/V Acetonitrile (ACN) to Water (with 1% Glacial Acetic Acid) under an isocratic elution at 1 mL/min, detection at 420 nm, and a reference standard. The method exhibited notable accuracy, precision, and reproducibility. Antioxidant potential, assessed through DPPH, nitric oxide, and hydroxyl radical scavenging assays, unveiled significant total phenol and total flavonoid quantities, highlighting C. longa’s potent antioxidant capacity. The study demonstrated a correlation between antioxidant activities and phenolic and flavonoid concentrations, reinforcing the robustness of our method. In conclusion, this method offers an effective means of quantifying curcumin within C. longa rhizomes and holds promise as a valuable tool for maintaining quality control in the production of this botanical material.
Keywords: curcuma longa L.; hplc method; validation; quality control; physicochemical screening; antioxidant activity